Apical microleakage of epoxy resin and methacrylate resin-based sealer with continuous wave obturation technique - Haslinda Haslinda; Christine A. Rovani; Aries C. Trilaksana (DiscoverSys Inc., 2016)
The aim of this research was to determine the microleakage apical sealer based on epoxy resin and methacrylate resin with continuous wave obturation technique.Thirty permanent lateral incisors were selected at random and divided into 3 groups (N=10), namely AH Plus obturator group (epoxy resin), EndoREZ group (methacrylate resin), and negative control. The samples were decoronated, root canal preparation, then kept in incubator of 37°C for 72 hours. Sample were coated with nail varnish then immersed in methylene blue for 48 hours. The samples were washed with distilled water, dried and nail varnish removed. The samples were clearing. Penetration was measured using microscope and given score 0-4. Measurements were analyzed statistically. By using Kruskal Wallis test and Mann Whitney test, there is no significant difference between the apical microleakage of the the epoxy resin root canal sealer with methacrylate root canal sealer based (p>0,05). It means that the apical microleakage of the epoxy resin root canal sealer based comparable with merhacrylate root canal sealer based. It was concluded that the apical microleakage of epoxy resin based sealer does not different to the methacrylate resin based sealer